Unveiling the best immune checkpoint inhibitor-based therapy for metastatic renal cell carcinoma in the first-line setting: an updated systematic review and Bayesian network analysis - Junpeng Wang; Xin Li; Mengjun Li; Qingyuan Liu; Zixuan Xie; Xiaotian Si; Lei Yang; Zhifeng Wang; Degang Ding (Therapeutic Advances in Medical Oncology)
Background: Immune checkpoint inhibitor (ICI)-based combination therapies have been recommended as first-line options for metastatic renal cell carcinoma (mRCC); however, no head-to-head randomized controlled trials (RCTs) have compared all existing ICI-based therapies. Objective: We aimed to analyze the updated data to compare the efficacy of all available ICI-based options for mRCC. Design: A systematic review and Bayesian network analysis. Data sources and methods: A systematic literature search was undertaken up to September 15, 2024, and subsequent analysis was performed using a Bayesian fixed-effect model. Results: This study included 30 RCTs involving 14,959 patients. The results revealed that nivolumab plus cabozantinib (hazard ratio (HR): 0.77; 95% credible interval (CrI): 0.63–0.93), pembrolizumab plus lenvatinib (HR: 0.79; 95% CrI: 0.64–0.99), toripalimab plus axitinib (HR: 0.62; 95% CrI: 0.42–0.97), nivolumab plus ipilimumab (HR: 0.72; 95% CrI: 0.62–0.84), pembrolizumab plus axitinib (HR: 0.84; 95% CrI: 0.71–0.98), and avelumab plus axitinib (HR: 0.79; 95% CrI: 0.64–0.98) were significantly more effective than sunitinib for overall survival (OS). Most ICI-based combination treatments resulted in fewer or similar high-grade adverse events compared to sunitinib, except for pembrolizumab plus lenvatinib. For favorable-risk patients, ICI-based combination therapies were not more effective than sunitinib in OS, while six ICI-based combination therapies were associated with significantly improved OS compared to sunitinib for intermediate-risk or poor-risk patients. Conclusion: Our findings demonstrated that combination therapies including nivolumab plus cabozantinib, pembrolizumab plus lenvatinib, toripalimab plus axitinib, nivolumab plus ipilimumab, pembrolizumab plus axitinib, and avelumab plus axitinib significantly improved OS versus sunitinib. For subgroup analysis, ICI-based combination therapies exhibited significant advantages over sunitinib for intermediate-risk or poor-risk patients, while such advantages were diminished in treating favorable-risk patients.